Landschap als erfgoed. Historische processen en gelaagde landschappen (Bulletin KNOB, 2011)
During the twentieth century, the man-made landscape was gradually discovered as cultural heritage. At first, the leading idea was, that the man-made landscape was the result of a slow process leading up to a 'climax' in the nineteenth century. Since then, landscapes have been changing at an increasing speed. Conservation aimed at protecting the 'traditional' landscapes that had more or less survived the twentieth century. During the 1980s new research showed that many landscapes had a dynamic and often troubled history. Mapping methods were developed, showing the landscape as a collection of objects, each with its own history. Although these methods saw landscape history as dynamic, they were at the same time reductionist visions, losing sight of the landscape as a whole. In recent years new methods, such as the 'biographical' approach, have opened new perspectives on the management of landscapes with complex histories.A special tool for research as well as for planning is the metaphor of historical layers in the landscape. It is evident that layers do not only exist in the archaeological sense (vertical layers, that can be peeled off to reach older traces), but also in a geographical sense (horizontal patterns as a result of, for example, innovation-diffusion). In other cases, traces of different periods are intermixed, when different activities took place on the same surface, each development erasing most earlier traces but at the same time leaving traces as a 'palimpsest'. Moreover, 'intellectual layers' can be distinguished where older periods are reactivated. Lastly, even objects that seem unchanged for many centuries, have received different functions and meanings in the course of time, making it possible to distinguish 'layers of meaning'.